2017
DOI: 10.1136/archdischild-2017-312798
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of estimating oral endotracheal tube insertion depth in newborns using weight or vocal cord guide

Abstract: ISRCTN39654846.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…Conversely, a 26 mm marking on 3.5 mm ETT represent an adequate distance only for term infants, and will be too long for moderately preterm newborns. This is in keeping with the results of Gill et al RCT comparing intubation according to depth marker or weight based formula where 49% of the preterm infants in the depth marker group had their ETT inserted too distally.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, a 26 mm marking on 3.5 mm ETT represent an adequate distance only for term infants, and will be too long for moderately preterm newborns. This is in keeping with the results of Gill et al RCT comparing intubation according to depth marker or weight based formula where 49% of the preterm infants in the depth marker group had their ETT inserted too distally.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple depth markers on ETT should be compared to commonly used patterns before being implemented. Another important comparison would be with other methods of assessment, such as formula, suprasternal palpation, and sonography . End‐points for clinical trials should not be limited to radiological position but would need to include procedural and respiratory adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was good to read Gill et al ’s1 report on a carefully conducted randomised trial examining methods to estimate endotracheal tube (ETT) length. Together with their group’s previous trial,2 neither use of the vocal cord guide nor a gestation-based formula showed superiority over the traditional 7-8-9 rule (Tochen’s formula).…”
mentioning
confidence: 99%